An effective heat dissipation strategy improving efficiency and thermal stability of phosphor-in-glass for high-power WLEDs. Issue 9 (1st May 2022) - Guo, Fan; Yuan, Rui; Yang, Yun-Ling; Zhao, Jing-Tai; Lin, Hui; Zhang, Zhi-Jun
Abstract: Phosphor-in-glass (PiG) is one of the most important spectral converters to overcome thermal effect in high-power white light-emitting diodes (LEDs). The Al2 O3 –SiO2 –B2 O3 –ZnO–Na2 O–Li2 O glass was designed and sintered with Y3 Al5 O12 :Ce 3+ (YAG: Ce) phosphors at the low temperature of 650 °C to obtain YAG: Ce-PiG. The optimized YAG: Ce-PiG shows the white light of the luminous efficiency (LE), correlated color temperature (CCT) and chromaticity coordinate (CIE) of 177.5 lm/W, 6410 K and (0.31, 0.34), respectively. The white LEDs (WLED) were fabricated by coupling the YAG: Ce-PiG with a blue light emitting chip, and the correlation between the luminescence properties, the thickness of PiG and the ratio of phosphors was investigated. More importantly, the WLEDs of a maximum luminous efficiency can reach up to 199.5 lm/W with the thickness of 0.35 mm. In addition, a structure with vacuum packaging technique based on the WLEDs lighting combined with sapphire as substrate was fabricated, which can effectively reduce the heat accumulation during the working process of WLEDs. Compared with normal non-vacuum packaging, the working temperature of WLEDs was reduced by about 35%, from 359.2 to 232.2 °C, with the novel vacuum packaging technique under 30W high-power chip and the luminous performance can still be maintained at 94.7%. In a word, the prepared YAG: Ce-PiG exhibits a great potential for application in high-power solid-state WLEDs. Highlights: The new glass matrix of Al2 O3 –SiO2 –B2 O3 –ZnO–Na2 O–Li2 O was designed and the thermal quenching effect of PiG was alleviated. The white LEDs fabricated using PiG with high thermal stability and luminous efficiency reach up to 199.5 lm/W. The vacuum packaging technique can significantly reduce heat accumulation in high-power white light-emitting diodes by 35%.